Thai Students Perspective of Online Learning Media during Covid-19 Pandemic - Hayuningtyas, Nina; Khodijah, Siti; Tehtae, Sareef; Karomah, Fitriatul (Journal of Language Intelligence and Culture, 2024)
The present qualitative study explores the perceptions of seven Thai undergraduate students in a university on the online learning medium when the COVID-19 pandemic hit this country. Semi-structured interviews were created to clarify the students' viewpoints on online learning medium. Thematic content analysis was used to analyze the transcriptions of the data collected from the online interviews. The study elicits three significant data themes that are connected to the research questions: the Thai students’ perception towards the online learning medium, their preference on the online learning medium, and the problems faced by them along using the online learning medium and the solving. Findings showed that the using of online learning mediums helped Thai students in lecturing during the COVID-19 pandemic. The most preferred online learning medium they use is WhatsApp application, followed by Google Meet as the second choice. They prefer WhatsApp to other online learning mediums or applications since it is stable, cheap, and easy to use. They also re-studied the lecturer’s explanation everywhere and anytime. The research found some problems students faced while using Google Meet or Zoom; the most common problem they faced was an unstable connection. While excessive internet data usage was another obstacle faced by them. To solve those problems, they frequently moved to another place providing free Wi-Fi or asked their friends or family to share the hotspot.